Accelerating the Crystallization of Zeolite SSZ‐13 with Polyamines. (23rd February 2022) - Dai, Heng; Claret, Jakob; Kunkes, Eduard L; Vattipalli, Vivek; Linares, Noemi; Huang, Chenfeng; Fiji, Muhammad; García‐Martinez, Javier; Moini, Ahmad; Rimer, Jeffrey D.
Abstract: Tailoring processes of nucleation and growth to achieve desired material properties is a pervasive challenge in synthetic crystallization. In systems where crystals form via nonclassical pathways, engineering materials often requires the controlled assembly and structural evolution of colloidal precursors. In this study, we examine zeolite SSZ‐13 crystallization and show that several polyquaternary amines function as efficient accelerants of nucleation, and, in selected cases, tune crystal size by orders of magnitude. Among the additives tested, polydiallyldimethylammonium (PDDA) was found to have the most pronounced impact on the kinetics of SSZ‐13 formation, leading to a 4‐fold reduction in crystallization time. Our findings also reveal that enhanced nucleation occurs at an optimal PDDA concentration where a combination of light‐scattering techniques demonstrate these conditions lead to polymer‐induced aggregation of amorphous precursors and the promotion of (alumino)silicate precipitation from the growth solution. Here, we show that relatively low concentrations of polymer additives can be used in unique ways to dramatically enhance SSZ‐13 crystallization rates, thereby improving the overall efficiency of zeolite synthesis. Abstract : A facile strategy is presented to modulate the rate of zeolite SSZ‐13 nucleation by regulating the evolution and colloidal stability of amorphous precursors using a small concentration of polymer additives, thus improving the overall efficiency of zeolite synthesis.